The popularity and usability of mobile applications for women and expecting mothers - Grądzik, Anna; Gorajek , Anna; Osiejewska, Aleksandra; Wojtachnio , Dominika; Nowakowska , Izabela; Bartoszewicz , Jakub (Journal of Education, Health and Sport, 2022)
Introduction and purpose: There are many applications for women, including those planning to conceive, being pregnant or having a small child. These applications have various functions, among others: menstrual cycle control, information about fetal development, labor contractions counting or lifestyle advice. Aim of the study was to assess the popularity, usability, most frequently used functions and expectations of users in relation to mobile applications designed for period tracking, for pregnant women and for parents. Material and methods: The study was conducted in the form of a self-prepared, anonymous survey shared on social media. Results: 522 correctly completed questionnaires were analysed. The main sources of knowledge about pregnancy and motherhood were: Internet (90.4%) and doctor (73.5%). 78.7% of participating women used period tracking applications. The most useful functions were: date of period (94.7%), fertile days and ovulation (86.4%) and menstrual cycle regularity (58,2%). 86.6% of women used pregnancy tracker applications. The most useful features were: information about week of pregnancy (98.5%), child development (95.3%) and countdown to childbirth (83%). Using application during pregnancy: 74.8% of women felt more aware and 68.6% enjoyed the expectation time more. Parenting applications were the least popular - only 25% of respondents used them. Conclusions: Thanks to the mobile applications, women can be more aware and better prepared for planning pregnancy and motherhood. Encouraging them to use the applications can bring many benefits in a doctor-patient relationships, provided that the information contained therein is properly constructed.